Phase II and Pharmacodynamic Study of Autophagy Inhibition Using Hydroxychloroquine in Patients With Metastatic Pancreatic Adenocarcinoma - Wolpin, Brian M. (AlphaMed Press, 2014)
BACKGROUND. Autophagy is a catabolic pathway that permits cells to recycle intracellular macromolecules, and its inhibition reduces pancreatic cancer growth in model systems. We evaluated hydoxychloroquine (HCQ), an inhibitor of autophagy, in patients with pancreatic cancer and analyzed pharmacodynamic markers in treated patients and mice. METHODS. Patients with previously treated metastatic pancreatic cancer were administered HCQ at 400 mg (n = 10) or 600 mg (n = 10) twice daily. The primary endpoint was 2-month progression-free survival (PFS). We analyzed peripheral lymphocytes from treated mice to identify pharmacodynamic markers of autophagy inhibition that were then assessed in peripheral lymphocytes from patients. RESULTS. Among 20 patients enrolled, 2 (10%) were without progressive disease at 2 months. Median PFS and overall survival were 46.5 and 69.0 days, respectively. Treatment-related grade 3/4 adverse events were lymphopenia (n = 1) and elevated alanine aminotransferase (n = 1). Tolerability and efficacy were similar at the two dose levels. Analysis of treated murine lymphocytes suggested that LC3-II expression by Western blot is a reliable marker for autophagy inhibition. Analysis of LC3-II in patient lymphocytes demonstrated inconsistent autophagy inhibition. CONCLUSION. Mouse studies identified LC3-II levels in peripheral lymphocytes as a potential pharmacodynamic marker of autophagy inhibition. In patients with previously treated metastatic pancreatic cancer, HCQ monotherapy achieved inconsistent autophagy inhibition and demonstrated negligible therapeutic efficacy.